Terapi Realitas Dan Konsep Sabar Dalam Physical Distancing Mahasiswi Di Asrama Astri Aulia - Ratna Wulan (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
Reality Therapy And Patience Concept In Physical Distancing Students At Astri Aulia Hostel. Covid-19 is a highly contagious disease that can shake an individual's psychological well-being. One way to break the chain of distribution is to live a clean lifestyle, wash hands, use masks and build physical distancing to stay at home and do all the activities in the house. Physical distancing, of course, will cause anxiety factors, because it narrows individual activities in the house, so this is where patience is needed to accept such needs. The research focuses on reality therapy and the concept of patience in carrying out physical distancing of female students at the Astri Aulia Yogyakarta dormitory. This research is a field research using qualitative descriptive methods. Data collection techniques are done by observation, interview and documentation. The results of the study are reality therapy and the concept of patience is able to have an impact on the client and in terms of religion, reality therapy is able to preserve patience in the lives of individuals to build physical distancing. Keywords: Physical Distancing; Patience; Reality Therapy